Thermal stability of InN epilayers grown by high pressure chemical vapor deposition - ALEVLİ, MUSTAFA (ELSEVIER SCIENCE BV, 2013)
The thermal stability of InN layers grown on sapphire by high-pressure chemical vapor deposition has been studied by thermal desorption, atomic force microscopy, X-ray diffraction, and infrared reflection measurements. Desorption products from samples grown with group V/III precursor ratios from 1200 to 4800, but otherwise identical growth conditions, have been monitored using differentially-pumped mass spectrometry while the sample temperature was ramped from room temperature to 825 degrees C. No significant desorption of nitrogen from the surface was observed below 630 degrees C, with a rapid increase of desorption of molecular nitrogen at substrate temperatures above 630 degrees C. No significant desorption of NH*/NH2* fragments was observed. From Arrhenius plots, the activation energy for desorption of nitrogen was found to be 1.6 +/- 0.2 eV. It was observed that the activation energy for the desorption of nitrogen from InN samples was independent of V/III precursor ratio. However, the temperature corresponding to the maximum desorption was found to be dependent on V/III precursor ratio, increasing from 749 degrees C for V/III precursor ratio of 1200 to 776 degrees C for V/III precursor ratio of 4800. The observed shift in the peak desorption temperature with increasing group V/III precursor ratio is attributed to the decrease in extended defects and the increase in grain size. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Indium nitride; InN; Mass spectrometry; Desorption; Activation energy; MOLECULAR-BEAM EPITAXY; INDIUM NITRIDE; GAN DECOMPOSITION; THIN-FILMS; LAYERS; H-2; AMBIENT; SYSTEM; SENSOR; N-2